BIODEGRADABLE POLYESTERS BASED ON RENEWABLE POLYOLS AND THEIR ANTI FUNGAL PROPERTIES DERIVED FROM SALVIA HISPANICA SEEDS - A. Jeni,; S. Begila David, (The Bioscan, 2025)
A new field of study is the use of bio-based materials to create sustainable goods. The use of renewable biomass-derived monomers in the production of green plastics has grown in popularity recently. One of the most important renewable resources that may be obtained in large quantities from a variety of natural and synthetic sources for the production of polyesters is polyols. Renewable polyols for the production of bio-based, biodegradable polyesters are covered in this study. Polyols and diacids, which are very ecologically friendly compounds, are produced as the polyesters break down. Certain elastomeric sustainable polyol-based polyesters may be developed by careful process engineering conditions selection, chemical adjustments, and creative technologies with an industrial focus.